Women Language in Mean Girls Movie Script by Tina Fey - Darman (ELITE: Journal of English Language and Literature, 2019)
This research entitled Women Language in Mean Girls Movie Script, aims to classify the women language features and the functions based on Lakoff’s theory found in Women Language in Mean Girls Movie Script by Tina Fey based on Lakoff’s theory. The data is collected through downloading movie script and movie, reading the movie script, watching and checking movie script, screen shooting the movie, the last is coding and classifying the features and functions of women’s language. Technique of data analysis is done through presenting, describing, interpreting, and concluding the data. Based on the finding and discussion, the researcher concludes there are ten features of women language, the researcher found ten features used by the character in the Mean Girls movie script. They are lexical hedges or filler 7 data, tag questions 3 data, rising intonation on declaratives 2 data, empty adjectives 2 data, avoidance of strong swear words 2 data, empathic stress 1 data, super polite forms 1 data, precise color terms 1 data, hypercorrect grammar 1 data, and intensifiers 1 data. Then, there are five language functions, but the researcher only found four functions in the Mean Girls movie script. They are to express uncertainty 3 data, to get response 5 data, to soften utterance 4 data, and to express feelings 9 data.